The Impact of Foreign Direct Investment (FDI) on Gross Domestic Production (GDP) in Indian Economy - Pratibha S.Gaikwad (Information Management and Business Review, 2013)
In this study, an attempt has been made to analyze the effects flow of foreign direct investment (FDI) arising from the implementation of liberalization polices (economic reform) on the gross domestic production (GDP) growth in Indian economy using a Cobb–Douglas production function and ARDL method during the period 1990-2008. The empirical results show that in the long run there exists a long-run relationship among the growth of gross domestic production and its major determinants of the labour force, the real capital and the real foreign direct investment. Finding indicates that foreign direct investment has positive effect but small significant on Gross Domestic Production, while the labour force and capital have had the most effect on gross domestic production.